Implementation Approaches for Project Planning.1 - Nutt, Paul C. (Academy of Management Review, 1983)
This paper relates the project planning process and implementation. An implementation approach is determined by the manager's choice of power bases to be applied and techniques to be used lo enhance the prospects of plan adoption. Sixteen planning environments are defined by the degree of centralization, amount of complexity, type of production, and emphasis on efficiency. A framework is proposed that suggests an implementation approach for each of the environments.